Oncocytic carcinoma of minor salivary gland: a case report - Samantaray, Sagarika; Panda, Sasmita; Dash, Sashibhusan; Rout, Niranjan (International Journal of Research in Medical Sciences, 2016)
Oncocytic carcinoma is an extremely rare malignancy of minor salivary gland. The biological behaviour, management and prognosis are not well established due to its rarity and paucity of published literature. We report a case of 32 year old man presented an ulcerated growth measuring 1cm in size in right buccal mucosa along with enlarged left submandibular lymphadenopathy. The diagnosis was suggestive of oncocytic carcinoma of minor salivary gland by cytology and subsequently confirmed by excisional biopsy.